2015
DOI: 10.1111/1471-0528.13222
|View full text |Cite
|
Sign up to set email alerts
|

Traction force during vacuum extraction: a prospective observational study

Abstract: Objective To investigate the traction force employed during vacuum extractions.Design Observational cross-sectional study.Setting Obstetric Department, Karolinska University Hospital, Sweden, and the Swedish National Congress of Obstetrics and Gynaecology, 2013.Population Two hundred women with vacuum extraction at term and 130 obstetricians participating in a simulated setting.Methods In a normal clinical setting, we used a specially adapted device to measure and record the force used to undertake vacuum extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 21 publications
1
33
1
Order By: Relevance
“…[26]. In our previous study[8], we observed a seven percent prevalence of (mild) hypoxic ischemic encephalopathy in strong category extraction. There is also some data suggesting that hypoxic encephalopathy and subgaleal hematoma might be comorbid conditions[29].…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…[26]. In our previous study[8], we observed a seven percent prevalence of (mild) hypoxic ischemic encephalopathy in strong category extraction. There is also some data suggesting that hypoxic encephalopathy and subgaleal hematoma might be comorbid conditions[29].…”
Section: Discussionmentioning
confidence: 85%
“…Two studies on plastic cup extractions suggest that the majority of deliveries require no more than the force equivalent to 11,5 kg (approximately 112 Newton)[6, 7]. Our research group found a different result in an observational study of 200 metal cup extractions, with average peak traction forces of 176, 225 and 241 N, depending on subjective category as easy, average or strong extraction respectively[8]. …”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Contrasting instrumental delivery where the head is pulled out by a stronger force in a relatively short period of time resulting in rapid descent of the fetal head and shoulders through the pelvis [20, 23]. It was estimated that during a vacuum extraction, the traction force on the fetus is up to 294 N [24], nine times higher than the usual force of spontaneous delivery [25]. This may result in the shoulders, especially the posterior shoulder, not descending along the curved sacral path synchronously with the pulled head.…”
Section: Discussionmentioning
confidence: 99%